2010
DOI: 10.1111/j.1600-0668.2010.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of particulate matter size distributions and indoor concentrations from kerosene and diesel lamps

Abstract: Changing lighting technologies to achieve increased efficiency and energy service levels can provide ancillary health benefits. The cheapest, crudest kerosene lamps emit the largest amounts of PM(2.5). Improving affordability and access to better lighting options (hurricane or pressure lamps and lighting using grid or off-grid electricity) can deliver health benefits for a large fraction of the world's population, while reducing the economic and environmental burden of the current fuel-based lighting technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…The low viscosity and surface tension of kerosene is implicated in easily allowing it to be aspirated into the lungs of persons exposed to and causing the effects described above particularly the lipoid pneumonitis. Organization (WHO) PM 2.5 concentration guideline was exceeded by at least an order of magnitude for all simple wick lamp burn rates with only one simple wick lamp [42,44]. Use of more than one lamp resulted in an increase in the total intake contribution from the fuel-based lamp The cheapest and crudest kerosene lamps were found to emit the largest amounts of PM 2.5 .…”
Section: Pulmonary System Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…The low viscosity and surface tension of kerosene is implicated in easily allowing it to be aspirated into the lungs of persons exposed to and causing the effects described above particularly the lipoid pneumonitis. Organization (WHO) PM 2.5 concentration guideline was exceeded by at least an order of magnitude for all simple wick lamp burn rates with only one simple wick lamp [42,44]. Use of more than one lamp resulted in an increase in the total intake contribution from the fuel-based lamp The cheapest and crudest kerosene lamps were found to emit the largest amounts of PM 2.5 .…”
Section: Pulmonary System Effectsmentioning
confidence: 97%
“…This may be attributed to emissions of toxic fumes into the air that consist of small fine particulates, polyorganic and polyaromatic hydrocarbons (PAH), carbon monoxide (CO), nitric oxides (NOs), sulphur dioxide (SO 2 ) and formaldehyde that induce tissue inflammation and oxidative stress[2]. There is strong and consistent evidence showing the release of particulate matter (PM) from kerosene combustion of median aerodynamic diameter of well below 2.5µm (PM 2.5 ), the size of which majority deposit in the deep lungs increasing the risk of respiratory diseases[2,[41][42][43]. Studies conducted recently in Kenya and Nigeria that characterized CO, CO 2 , NO x , PM size distributions and indoor concentrations from kerosene and diesel lamps found out that the 24-h World Health…”
mentioning
confidence: 99%
“…VanVliet et al (2013) offers one of the only studies to measure lighting-related particulates in actual occupied homes, and found a significant contribution from kerosene lanterns above that traced to biofuels used for cooking. Measurements by Apple et al (2010) demonstrated that night vendors who use a single simple wick lamp in simulated high-air-exchange market kiosks will likely be exposed to dangerous PM2.5 concentrations that are an order of magnitude greater than ambient health guidelines (WHO, 2006). Thanks to more efficient combustion, using a hurricane lamp will reduce exposure to PM2.5 and PM10 concentrations by an order of magnitude compared to a simple wick lamp.…”
Section: Indoor Air Pollutionmentioning
confidence: 98%
“…In several of the most populated African countries, including Uganda, Ethiopia, and Kenya, more than 60 % of the population relies on kerosene as the primary lighting fuel (Apple et al, 2010;IFC/WB, 2008;UBOS, 2010).…”
Section: Kerosene Lampsmentioning
confidence: 99%